Cookie isento de glúten obtido com biomassa e farinha de banana (Musa paradisíaca) verde - Oliveira, Adriana de (2014)
The green banana flour is a source of potassium, proteins A and B. In its composition about 55% to 93% of total solids is composed of resistant starch (RS) and fiber. Biomass is obtained from the decoction of green banana and is also rich in fiber and act us many problems of the intestine. The development of gluten -free products, from biomass and green banana flour is of great importance, as these have important rheological characteristics. Moreover, it represents a new option to use a significant portion of the population that has restrictions on the consumption of products containing gluten. This study aimed to develop a gluten-free cookie made from biomass and green banana flour. Three different formulations were prepared cookies, and the received Formulation I 50% green banana flour and 50% biomass, Formulation II was added 100% green banana flour and Formulation III was added 25% Flour Green banana and 75% biomass. After obtaining the cookie physico-chemical parameters were evaluated by the yield (weight, thickness and diameter), chemical composition (ash, Moisture, lipid, protein and carbohydrate) and color evaluation. Were also performed microbiological analysis of thermotolerant coliforms, coagulase positive Staphylococcus and Salmonella spp. Later sensory analysis was performed with 74 judges applying the Hedonic Scale Testing for the attributes color, sweetness, texture and overall impression. The results of chemical and microbiological parameters for all formulations presented in accordance with current legislation. In the evaluation of performance parameters, no significant differences were observed. As for sensory analysis, no significant difference (p ≤ 0.05) compared to attributes. In evaluating only the color parameter L* significant difference (p ≤ 0.05). Therefore it is concluded that it is possible to obtain gluten-free products based biomass and green banana flour, which meet the needs of patients with celiac disease or gluten intolerant.